Experimental investigation of PCM location in a commercial display cabinet cooled by a transcritical CO2 system - YILMAZ, BARIŞ; MANÇUHAN, EBRU (ELSEVIER SCI LTD, 2020)
In this study, the influence of phase change material (PCM) location in a closed display cabinet cooled by a transcritical CO2 refrigeration system was examined experimentally. Two configurations have been investigated where PCM panels are placed on the backside and the shelves of the cabinet. The effect of PCM locations on the cabinet air temperature and compressor power consumption is evaluated and compared during periods of 24 and 8 h of operation. The variation of in the cabinet air temperatures and power consumption with time is measured during charging, running, and power failure periods. It is found that installing PCMs on the shelves of the cabinet is more advantageous and promising in terms of both maintaining cabinet air temperature homogeneous and keeping it at certain average temperature levels. For PCM on the shelves case, energy saving is found 4.4% less than without PCM case. On the other hand, PCM on the backside case results in 8% more energy consumption. Moreover, the running time is found 15.8 less for PCM on the shelves case. Therefore, PCM on shelves case is concluded to be the best option for PCM utilization in the present study. (C) 2020 Elsevier Ltd and IIR. All rights reserved.
Keywords: Phase change material; Display cabinet; Energy consumption; Power failure; Experiment; PHASE-CHANGE MATERIALS; PERFORMANCE